Do Social Pension Schemes Promote the Mental Health of Rural Middle-Aged and Old Residents? Evidence From China - Pan, Guochen; Li, Shaobin; Geng, Zhixiang; Zhan, Kai (Frontiers in Public Health, 2021)
As China experiences rapid aging, the mental health issue of older rural adults becomes a major concern of public health. Among other social insurance programs, the New Rural Social Pension (NRSP) scheme was established to replace part of the income for the rural residents in old age in China. This article employs survey data of China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2018 to investigate the impact of pension on depression of middle-aged and old residents. Our results show that the pension scheme not only reduces the depressive symptoms of the rural residents, but holds down the prevalence rate of depression. Among the subscribers of the pension scheme, the pensioners benefit more from enrolling in the pension scheme than the contributors in term of depression alleviation. The impact of pension on depression displays heterogeneity, female residents, residents in central China and/or those from lower income household are found to be positively affected. It is also confirmed that pension scheme contributes to easing depression via reduced labor supply, better family supports, and more consumption expenditure.